Personnel Éducatif Du Secteur Public Et Activités Lucratives Parallèles En Côte d’Ivoire - Koffi Affoué Philomène (European Scientific Journal, ESJ, 2017)
The quality of education is based on the content of the lessons which depends on the interest of educators in their profession through their availability for work and learners. In Côte d'Ivoire, this availability is not always effective, since many educational staff in public secondary schools carry out lucrative activities in parallel with their professional activities. This article "public sector educators and parallel lucrative activities in Côte d'Ivoire", which aims to explain how these activities influence the quality of education, is based on a survey based on qualitative methods And in quantitative terms in ten (10) secondary public schools in Abidjan. The survey involved interviewing 274 educators with teachers, management, management and union leaders through accidental sampling for the quantitative method and saturation sampling for the qualitative method. Interviews were conducted using semi-structured interview guides, while questionnaires were administered on the basis of standardized questionnaires on quantitative techniques. The results of the survey show that the lucrative activities of educational staff influence their attendance and contribute to the non-completion of school programs. These activities, which are also a source of exhaustion, undermine the efficiency of the educational staff of public secondary schools. The fatigue resulting from these activities does not always favor a better performance of the educational staff in the school while they negatively influence the integration of the values in the learners. In this way, the lucrative activities of educational staff contribute to the poor quality of education in Côte d'Ivoire. They should therefore be reorganized in order to achieve a quality education system as sought by the Ivorian educational community.